2019
DOI: 10.3390/cancers11091299
|View full text |Cite
|
Sign up to set email alerts
|

AT2 Receptor Mediated Activation of the Tyrosine Phosphatase PTP1B Blocks Caveolin-1 Enhanced Migration, Invasion and Metastasis of Cancer Cells

Abstract: The renin–angiotensin receptor AT2R controls systemic blood pressure and is also suggested to modulate metastasis of cancer cells. However, in the latter case, the mechanisms involved downstream of AT2R remain to be defined. We recently described a novel Caveolin-1(CAV1)/Ras-related protein 5A (Rab5)/Ras-related C3 botulinum toxin substrate 1 (Rac1) signaling axis that promotes metastasis in melanoma, colon, and breast cancer cells. Here, we evaluated whether the anti-metastatic effect of AT2R is connected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…In the patients with advanced colon cancer, the defects of the above therapy are obvious resulting in a poor prognosis. Postoperative metastasis for colon cancer chiefly includes hematological metastasis, peritoneal metastasis and distant lymph node metastasis, which are frequently accompanied by local recurrence [4]. Hematogenous metastasis is the dominating cause of failure in the treatment of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the patients with advanced colon cancer, the defects of the above therapy are obvious resulting in a poor prognosis. Postoperative metastasis for colon cancer chiefly includes hematological metastasis, peritoneal metastasis and distant lymph node metastasis, which are frequently accompanied by local recurrence [4]. Hematogenous metastasis is the dominating cause of failure in the treatment of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Ang II increased the phosphorylation of the extracellular signal-regulated protein kinase 1/2, c-jun-N-terminal kinase 1/2, or p38 mitogen-activated protein kinases, signaling pathways involved on cell proliferation and particularly relevant for cancer development [67,68] (Figure 2). Notably, in fibroblasts, Ang II binding to AT1R results in Smad2 and Smad3 phosphorylation via the ERK/p38/MAPK pathway, increasing the activation of the TGFβ1/Smad2/Smad3/Smad4 signaling [69]. Telmisartan, an AT1 receptor antagonist, significantly inhibited the growth of the non-small cell lung cancer (NSCLC) A549 cell line, in a time-and dose-dependent manner and led to an increase of the pro-apoptotic proteins caspase-3 and Bcl-xL [70].…”
Section: Ace/ang Ii/at1 Receptor Axismentioning
confidence: 99%
“…Notably, nanoparticle-based AT2 receptor gene transfection, which markedly increased AT2 receptor expression, resulted in increased cell death of the human lung cancer cell line A549 [81]. The activation of AT2 receptor signaling has been described to produce antiproliferative, survival-promoting, as well as migratory, pro-invasive effects due to phosphatase-mediated (phosphotyrosine phosphatase PTP, protein tyrosine phosphatase 1B, PTP1B, and protein phosphatase 2A, PP2A) dephosphorylating events, through an inhibitory effect on Ras and MEK1/2 proteins of the Smad and MAPK pathways (PTP and PP2A) and by PTP1B-mediated novel Caveolin-1 (CAV1) dephosphorylation and inhibition of the CAV1/Rab5/Rac-1 pathway [69,85] (Figure 2).…”
Section: At2 Receptormentioning
confidence: 99%
“…The B16/ F10 mouse melanoma cell line is an exception and possesses only AT 2 Rs. [68][69][70][71] Normal melanocytes express exclusively AT 1 Rs. [2,69]…”
Section: Angiotensin Receptor Expression In Skin Cancermentioning
confidence: 99%
“…[ 69 ] However, even though this study provided a whole set of data, which consistently supported the authors’ conclusions, the more common notion on the role of angiotensin receptors in cancer in the scientific literature is that the AT 1 R acts pro‐proliferative, while the AT 2 R is a tumor suppressor that inhibits proliferation, migration and metastasis. [ 72,73 ] In fact, another very recent study by Martinez‐Meza et al [ 71 ] reported that selective stimulation or overexpression of AT 2 Rs in mouse B16/F10 and human A375 melanoma cells reduced “normal” and transendothelial migration. The view that AT 2 Rs have anti‐cancer effects is supported by the fact that an AT 2 R‐binding protein, ATIP (also termed MTUS) has been identified to be a tumor suppressor protein.…”
Section: The Cutaneous Renin‐angiotensin System Under Pathophysiologimentioning
confidence: 99%